Retracer notre ciel - Mathilde Chauvel; Caroline Dejoie; Isaline Dupond Jacquemart; Manon Lecaplain; Mathilde Leïchlé; Laboratoire Corps genre arts de l’association EFiGiES (Glad!)
Feed back on a virtual exhibition organized by the Laboratoire Corps, genre, arts, part of the association EFiGiES, at the beginning of 2021.